2015
DOI: 10.1155/2015/835767
|View full text |Cite
|
Sign up to set email alerts
|

Beninese Medicinal Plants as a Source of Antimycobacterial Agents: Bioguided Fractionation andIn VitroActivity of Alkaloids Isolated fromHolarrhena floribundaUsed in Traditional Treatment of Buruli Ulcer

Abstract: Buruli ulcer (BU) imposes a serious economic burden on affected households and on health systems that are involved in diagnosing the disease and treating patients. Research is needed to find cost-effective therapies for this costly disease. Plants have always been an important source of new pharmacologically active molecules. Consequently we decided to undertake the study of plants used in traditional treatment of BU in Benin and investigate their antimycobacterial activity as well as their chemical compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 5 publications
1
28
0
2
Order By: Relevance
“…Previous studies showed that extracts and fractions from stem bark of H. floribunda had a good in vitro antiplasmodial activity against the chloroquine-resistant strain FCR-3 isolated from Gambia and the chloroquine-sensitive standard strain 3D7 (Fotie et al, 2006). This activity could be related to the plant alkaloids contents (Janot et al, 1959;Yemoa et al, 2015). According to Saxena et al (2003) and Ramazani et al (2010) several classes of secondary metabolites are responsible for the antimalarial activity, but the most important and diverse potential bioactivity has been observed with alkaloids.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies showed that extracts and fractions from stem bark of H. floribunda had a good in vitro antiplasmodial activity against the chloroquine-resistant strain FCR-3 isolated from Gambia and the chloroquine-sensitive standard strain 3D7 (Fotie et al, 2006). This activity could be related to the plant alkaloids contents (Janot et al, 1959;Yemoa et al, 2015). According to Saxena et al (2003) and Ramazani et al (2010) several classes of secondary metabolites are responsible for the antimalarial activity, but the most important and diverse potential bioactivity has been observed with alkaloids.…”
Section: Discussionmentioning
confidence: 95%
“…It grows as a shrub or a tree. The plant is widely distributed in West Africa, where several parts of the plant are used for medicinal purposes (Yemoa et al, 2015). The stem-bark and leaves are used to treat various diseases including malaria, fever, dysentery, amoebic diseases, diarrhoea, sterility, amenorrhea and diabetes (Bouquet & Debray, 1974; Kerharo & Adam, 1974;Arbonnier, 2000;Fotie et al, 2006;Bayala et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Extraction methods generally mimic herbal practitioners' approach to prepare decoctions or infusions using mainly water and palm wine (Yemoa et al, 2014(Yemoa et al, , 2011Addo et al, 2007;Kone et al, 2007Kone et al, , 2009. Other extraction procedures include the use of ethanol or organic solvents of increasing polarity (hexane, dichloromethane, ethyl acetate and water) to partition plant materials.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…C'est ainsi que de nombreux malades ont recours, très souvent, et en première intention, à la médecine traditionnelle et aux plantes pour traiter cette pathologie (Johnson et al, 2004;Renzaho et al, 2007;Porten et al, 2009;Yemoa et al, 2008Yemoa et al, , 2015. Des travaux ont été entrepris pour mieux étudier ces plantes et thérapies traditionnelles afin de disposer des informations par rapport à l'efficacité et/ou l'innocuité de ces dernières.…”
Section: Introductionunclassified
“…Des travaux ont été entrepris pour mieux étudier ces plantes et thérapies traditionnelles afin de disposer des informations par rapport à l'efficacité et/ou l'innocuité de ces dernières. Plusieurs espèces de plantes médicinales traditionnellement utilisées pour traiter l'UB ont été identifiées, leur composition chimique définie et leurs activités antibactériennes sur Mycobacterium ulcerans, ainsi que leur toxicité déterminées en Afrique de l'Ouest de manière globale (Tsouh Fokou et al, 2015, et plus spécifiquement au Benin (Yemoa et al, 2008(Yemoa et al, , 2011(Yemoa et al, , 2015, au Ghana (Addo et al, 2007), en Côte d'Ivoire (Coulibaly et al, 2011). Au Cameroun, les travaux de Pouillot et al (2007), Landier et al (2011) soit par massage et désinfection de la lésion avec les décoctions préparées (64,3%), soit par application locale en cataplasme (14,3%) ou par badigeonnage (3,6%), soit par projection sur les lésions ou plaies ulcéreuses, de la préparation contenue dans des fragments de feuilles de bananier préalablement ramollies au feu de bois (14,3%).…”
Section: Introductionunclassified